Examining integrated leadership systems in high schools: connecting principal and teacher leadership to organizational processes and student outcomes. Issue 3 (3rd July 2017) - Sebastian, James; Huang, Haigen; Allensworth, Elaine
ABSTRACT: Research on school leadership suggests that both principal and teacher leadership are important for school improvement. However, few studies have studied the interaction of principal and teacher leadership as separate but linked systems in how they relate to student outcomes. In this study, we examine how leadership pathways are related in the context of high schools and compare findings to research in elementary schools. Using survey and administrative data from high schools in a large urban context, the paper explores direct and indirect pathways from leadership to student achievement growth. The results indicate that there are 2 pathways through which principal leadership is related to student learning in high schools. One pathway is mediated by teacher leadership, whereas the second pathway does not include teacher leadership. We find that similar to elementary schools, the learning climate is the only organizational factor that links principal and teacher leadership with student achievement.